A technical review of face mask wearing in preventing respiratory COVID-19 transmission. (April 2021) - Liao, Mingrui; Liu, Huayang; Wang, Xi; Hu, Xuzhi; Huang, Yuhao; Liu, Xuqing; Brenan, Keith; Mecha, Jared; Nirmalan, Mahesan; Lu, Jian Ren
Abstract: Since the outbreak of the COVID-19 pandemic, most countries have recommended their citizens to adopt social distance, hand hygiene, and face mask wearing. However, wearing face masks has not been well adopted by many citizens. While the reasons are complex, there is a general perception that the evidence to support face mask wearing is lacking, especially for the general public in a community setting. Face mask wearing can block or filter airborne virus-carrying particles through the working of colloid and interface science. This paper assesses current knowledge behind the design and functioning of face masks by reviewing the selection of materials, mask specifications, relevant laboratory tests, and respiratory virus transmission trials, with an overview of future development of reusable masks for the general public. This review highlights the effectiveness of face mask wearing in the prevention of COVID-19 infection. Graphical abstract: Image 1